The Biosynthetic Gene Cluster for Andrastin A in Penicillium roqueforti - Rojas-Aedo, Juan F.; Gil-Durán, Carlos; Del-Cid, Abdiel; Valdés, Natalia; Álamos, Pamela; Vaca, Inmaculada; García-Rico, Ramón O.; Levicán, Gloria; Tello, Mario; Chávez, Renato (Frontiers in Microbiology, 2017)
Penicillium roqueforti is a filamentous fungus involved in the ripening of several kinds of blue cheeses. In addition, this fungus produces several secondary metabolites, including the meroterpenoid compound andrastin A, a promising antitumoral compound. However, to date the genomic cluster responsible for the biosynthesis of this compound in P. roqueforti has not been described. In this work, we have sequenced and annotated a genomic region of approximately 29.4kbp (named the adr gene cluster) that is involved in the biosynthesis of andrastin A in P. roqueforti. This region contains ten genes, named adrA, adrC, adrD, adrE, adrF, adrG, adrH, adrI, adrJ and adrK. Interestingly, the adrB gene previously found in the adr cluster from P. chrysogenum, was found as a residual pseudogene in the adr cluster from P. roqueforti. RNA-mediated gene silencing of each of the ten genes resulted in significant reductions in andrastin A production, confirming that all of them are involved in the biosynthesis of this compound. Of particular interest was the adrC gene, encoding for a major facilitator superfamily (MFS) transporter. According to our results, this gene is required for the production of andrastin A but does not have any role in its secretion to the extracellular medium. The identification of the adr cluster in P. roqueforti will be important to understand the molecular basis of the production of andrastin A, and for the obtainment of strains of P. roqueforti overproducing andrastin A that might be of interest for the cheese industry.